GEOLOGI DAN HIDROGEOLOGI DAERAH WERU DAN SEKITARNYA, KABUPATEN SUKOHARJO, PROVINSI JAWA TENGAH - Aji Pangestu, Ahmad
The research area is located in Weru District, Bulu District, and Tawangsari District, Sukoharjo Regency, and Manyaran District, Wonogiri Regency, Central Java, and Semin District, Gunung Kidul Regency, Yogyakarta. Geographically, the research area is located at UTM coordinates 474000–480000 mE and 9134000– 9143000 mS (WGS 1984, 49S zone). The research area is 54 km2. Based on the BMB classification, the research area can be divided into five geomorphological units, Tawangsari Lava Ridge Unit, Bulu Pyroclastic Mountains Unit, Manyaran Denudational Plain Unit, Semin Isolated Hills Unit, Weru Alluvial Plain Unit. Stratigraphically, the research area can be divided into six non-formal rock units which were formed during Late Oligocene–Recent, deposited in marine to fluvial environment. The sequence from older to younger strata are Andesite Unit, Breccia 1 Unit, Breccia 2 Unit, Sandstone Unit, Limestone Unit, and Alluvial Deposit Unit. Geological structures in the research area are Pundungrejo Normal Fault, Sanggang Normal Fault, Candirejo Normal Fault, Alasombo Normal Fault, Candirejo Strikslip Fault, Manyaran Syncline, and Candirejo Anticline. Aquifer in the research area is in the weathered Andesite Unit, weathered Breccia 1 Unit, Breccia 2 Unit, Sandstone Unit, Limestone Unit , and Alluvial Deposit Unit. The type of aquifer in the research area is unconfined aquifer. There 7 from 15 springs and 48 form 67 wells are suitable for drinking according to Peraturan Menteri Kesehatan No.492/MENKES/PER/IV/2010 based on pH and TDS value criteria. The pH value ranges from 5,7–8.9 while TDS value ranges from 84-700 mg/L.